Identification of proAKAP4 concentration variations in dromedary sperm and their correlation with monthly semen parameters. Issue 4 (15th November 2021) - Malo, Clara; Carracedo, Sara; Delehedde, Maryse; Sergeant, Nicolas; Skidmore, Julian Alexandra
Abstract : ProAKAP4 is synthetized as a precursor polypeptide that must be converted into mature AKAP4 in living spermatozoa and is considered as a functional marker of spermatozoa. The gene is well-conserved in mammals although uncharacterized in Camelidae. In the present study, we investigate the expression metabolism of proAKAP4 and AKAP4 proteins and evaluate their seasonal dynamics relative to semen quality in dromedary camels. Semen parameters including volume and viscosity and characteristics of sperm including concentration, total production, total and progressive motility, vitality, acrosome integrity and morphological abnormalities were assessed in semen samples collected weekly from six camels during the rutting season, from November to April. Only total sperm production varied, peaking in January. Both the precursor proAKAP4 and AKAP4 proteins were investigated and shown to express biochemical properties similar to those described in other mammals. ProAKAP4 concentrations expressed in ng/10 million spermatozoa as assayed using a specific ELISA showed a strong positive correlation with ejaculate volume ( P = 0.045), viscosity ( P < 0.001) and sperm total motility ( P = 0.049). Furthermore, their concentrations exhibited clear seasonal variations in camel semen. In conclusion, the assessment of proAKAP4 concentrations in camel sperm provides a novel parameter to assess sperm quality. Further studies should be performed to investigate proAKAP4 concentrations relative to fertility in Camelidae that may help to define the right time for mating and semen collection and increase the success of breeding programs. Lay summary: Breeding related to the seasons/time of year in the camel has been reported in several studies. A better knowledge of semen quality during the breeding season would assist in determining the best period for mating in camels. However, conventional sperm parameters are held to be unsatisfactory because they cannot predict breeding potential. ProAKAP4 a sperm-specific protein has been described as a functional marker of sperm and a key fertility marker in several species but has not been described in camels. Motility or membrane integrity parameters of semen collected throughout the breeding season and also the presence of proAKAP4 protein were investigated. ProAKAP4 was identified for the first time in camels and their concentrations exhibited clear seasonal variations in camel semen showing strong correlations with ejaculate volume and total motility and viscosity. Further studies should be performed to investigate proAKAP4 concentrations relative to fertility in camels to define the right time for mating and increase the success of breeding programs.